Sosialisasi Pemanfaatan Media Sosial Untuk Mengedukasi Remaja Tentang Bahaya Perkawinan Usia Dini - Sodirin, Sodirin; Mustakim, Senen; Zainudin, Bustami; Hudalil, Ahmad; Pinaloka, Redi (Devotion: Journal Corner of Community Service, 2025)
Tempeh is an original traditional food from Indonesia which is a cultural heritage of the noble culture of the Indonesian nation. Tempeh is a super food or food that is rich in nutrients. Tempeh innovation can be used as a variety of food that can increase the economic value of the community. Partners' problems include the lack of community skills on how to process tempeh into various kinds of foods that are attractive and have high nutritional value. The solution offered is to provide education and training on the skills of making various processed tempeh products, one of which is making tempeh chips. Community service activities are carried out with four stages of activities, namely identification, preparation, implementation and evaluation. Identification of the problems faced, preparatory activities include taking care of permits, the implementation of activities includes training in making tempeh chips as an effort to innovate products and demonstrations of making tempeh chips. Participants were enthusiastic in participating in the training until it was finished. The training on making tempeh chips as an effort to innovate products runs smoothly, can improve the community's economy and participants follow enthusiastically.